Pentosan polysulfate for the treatment of hemorrhagic cystitis after allogeneic hematopoietic cell transplant. (October 2022) - Hatch, Rachel V; Freyer, Craig W; Carulli, Alison; Luger, Selina M; Martin, Mary E; McCurdy, Shannon R; Porter, David L; Loren, Alison W
Introduction: Hemorrhagic cystitis can commonly occur following an allogeneic hematopoietic cell transplant and treatment options are currently limited. Pentosan polysulfate, a heparin-like, sulfated polysaccharide, is used to relieve bladder pain and discomfort associated with interstitial cystitis. Initial reports in patients with hemorrhagic cystitis demonstrate that pentosan polysulfate may hasten hemorrhagic cystitis resolution and control symptoms. Methods and results: This report includes a retrospective case series of six patients who received pentosan polysulfate for the treatment of hemorrhagic cystitis following an allogeneic hematopoietic cell transplant. Pentosan polysulfate was initiated at a median of 4.5 days (range: 3–18) following hemorrhagic cystitis onset and continued for a median duration of 17.5 days (range: 7–64). Four patients were tested for BK virus and all were found to have BK viremia and viruria around the time of pentosan polysulfate initiation. The median number of red blood cell transfusions seemed to decrease in the patients initiated on pentosan polysulfate. All patients received a multi-agent treatment regimen, which included pentosan polysulfate, and half the patients had symptom resolution. The median time to symptom resolution from pentosan polysulfate initiation was 9 days (range: 7–10). Conclusion: Pentosan polysulfate was well-tolerated and seemed to assist with symptom resolution. Future studies are needed to confirm the impact of pentosan polysulfate on the treatment of hemorrhagic cystitis.